Răspunsuri

Cel mai inteligent răspuns!
2014-05-10T22:32:52+03:00
{6√5x-2√3y=42       inmultim cu -3            {-18√5x+6√3y=-126
{5√5x-3√3y=23       inmultim cu 2              {10√5x-6√3y=46      ⇒se reduce y⇒

-18√5x+10√5x=-126+46   ⇒     -8√5x=-80   inmultim cu -1
x=80/8√5  simplificam  x=10/√5  rationalizam⇒x=10√5/5  simplificam⇒
x=2√5
inlocuim pe x in prima relatie si avem:
6√5·2√5-2√3y=42  ⇒    60-2√3y=42
-2√3y=42-60⇒     -2√3y=-18    inmultim cu -1⇒
y=18/2√3  simplificam⇒  y=9/√3   rationalizam⇒    y=9√3/3   simplificam
y=3√3
1 5 1